Status, crop losses, epidemiology, variability, and disease management of cumin blight: A review: Management of cumin blight - Balai, Laxman Prasad; Khardia, S M; Singh, Navab; Sethi, Indu Bala; Sharma, Sachin (Journal of Spices and Aromatic Crops, 2025)
Cumin (Cuminum cyminum L.) is a spice crop native to the eastern Mediterranean area and is now cultivated worldwide, especially in South Asia, North Africa, and Latin America. The most significant and destructive disease affecting cumin is blight caused by the pathogen Alternaria burnsii. This disease progresses after flowering, particularly during seed formation, and is exacerbated by cold, moist, and consistently gloomy weather. The pathogen grows to its maximum temperature of 28±1°C. The disease intensity has been found to range from 11.34 to 80.00 percent, depending on the climate. Symptoms of the disease manifest as small, isolated, whitish necrotic spots on aerial plant parts. These spots gradually enlarge and merge, causing the plant to turn purple, then brown, and ultimately black. Under ideal circumstances, the contagion quickly spreads to the plant’s stem and flowers, killing the viable leaves and flowers, which are typically non-viable and may not appear withered. It is essential to investigate blight, focusing on its symptoms, signs, biology, status, epidemiology, cultural variation, morphological, pathogenic, and molecular variability. Developing effective disease management technologies and improved resistance screening techniques are necessary to recognize the changes in disease scenarios in climate fluctuations. This review updates current knowledge regarding the pathogen symptomology, status, variability, and source of resistance has been reviewed and updated, identifying management options and the genetic basis of resistance as future research priorities.